1974
DOI: 10.1002/jrs.1250020405
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman scattering and vibronic coupling in aquo‐ and cyano‐cobalamin

Abstract: The resonance Raman spectra of cyano-and aquocobalamin have been obtained from aqueous solutions. In order to check the vibronic theory of Raman intensity in the rigorous resonance case, the excitation profile of the 1502 cm-' vibration was measured and analyzed using a model of two displaced harmonic oscillators for the ground and the resonant electronic state. A very good agreement is shown between the calculated and the experimental values of both the excitation profile and the absorption spectrum. Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Several approximations are introduced to evaluate fa: (a) harmonic oscillator wave functions are assumed for the g and e states, (b) it is assumed that no change in force constant occurs in the upper state, and (c) it is assumed that the potential energy curves are displaced from each other horizontally by a parameter x such that x = (Vb.,1,7r/h)1/2Q (4) Computer programs were written to calculate and plot the excitation profiles. The sum over u was taken up until u = 6.…”
Section: Theoreticalmentioning
confidence: 99%
“…Several approximations are introduced to evaluate fa: (a) harmonic oscillator wave functions are assumed for the g and e states, (b) it is assumed that no change in force constant occurs in the upper state, and (c) it is assumed that the potential energy curves are displaced from each other horizontally by a parameter x such that x = (Vb.,1,7r/h)1/2Q (4) Computer programs were written to calculate and plot the excitation profiles. The sum over u was taken up until u = 6.…”
Section: Theoreticalmentioning
confidence: 99%
“…The peak at 425 cm -1 , which may be assigned to Co-N bond stretching, disappears after 80 min, as shown in Figure 9(d). [44][45][46][47][48] It is implied that the Co-N bonds have been cleaved at this stage. The peak at 335 cm -1 , which is assigned to the adenine stretching vibration mode, disappears simultaneously.…”
Section: Investigation Of Reaction Kineticsmentioning
confidence: 99%
“…Therefore, RR spectroscopy was applied to monitor the process of TiO 2 -assisted photocatalytic decomposition of vitamin B 12 (Figure 9). Assignments were made on the basis of the RR spectra of vitamin B 12 , 35,[39][40][41][42][43][44][45][46][47][48] and the changes of characteristic peaks are listed in Table 2. The weak peak at 481 cm -1 in Figure 9(a), assigned to the Co-CN stretching vibration mode, does not appear in Figure 9(b).…”
Section: Investigation Of Reaction Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years there has been a growing activity, both experimental and theoretical, in the field of resonance Raman scattering (RRS) from molecules [1][2][3][4][5][6][7][8][9][10][11][12]. It has been shown that RRS is a very useful tool for the investigation of molecular properties in excited states.…”
Section: Introductionmentioning
confidence: 99%